Physiological variability in Verticillium fungicola isolates collected from different mushroom farms of Haryana state - Singh, Jagdeep; Mohan, Man; ., Mamta; Singh, Surjeet; Saharan, H S (Mushroom Research, 2021)
Verticillium fungicola is a serious pathogen causing dry bubble disease in button mushroom (Agaricus bisporus). Present investigations were carried out on different isolates of pathogen by covering an aspect of physiological variability in pathogen isolates. The isolates of V. fungicola collected from different mushroom farms of Haryana state, coded as MHS (Hisar), BFT (Fatehabad), NJN (Jind),RHT (Rohtak), TPN (Panipat), BSN (Sonipat), FDB (Fridabad) and SKK (Kurukshetra) and pathogenicity was proved on A. bisporus. All isolates showed physiological variations on PDA at pH regimes 6.0 - 7.5 and 15 - 25 °C temperature after 12 days of incubation. Among the evaluated isolates maximum growth was recorded in BSN (44.67 mm), followed by TPN (43.83 mm), FDB (43.33 mm),SKK (42.17 mm), RHT (41.50 mm) and NJN (38.00 mm), while the rest one such as MHS (35.83 mm)and BFT (34.83 mm) showed minimum radial growth at 25±1°C after 12 days of incubation. On the other hand, at 15±1°C the radial growth of all V. fungicola isolates was significantly reduced i.e.10.00 (BFT), 10.83 (MHS), 11.33 (NJN), 12.50 (RHT), 17.50 (TPN), 18.00 (BSN), 16.17 (FDB) and14.67 mm (SKK) after 12 days of incubation. V. fungicola isolates grow at pH regimes of 6.0 to 7.5.However, the maximum radial growth was achieved in all the isolates when pH was 6.5 followed by 6.0,7.0 and 7.5. Among isolates the maximum growth was recorded at pH 6.5 in BSN isolate (44.83 mm),followed by TPN (44.00 mm), FDB (42.17 mm), SKK (41.50 mm), RHT (41.33 mm) and NJN (38.50mm), while the minimum radial growth was recorded in isolates MHS (37.17 mm) and BFT (35.67mm) at 25±1°C after 12 days of incubation.